PP.19.29: RENAL DOPAMINE ALTERATION INCREASES NA+, K+-ATPASE EXPRESSION AND ACTIVITY AND CORRELATES WITH HYPERTENSION IN FRUCTOSE OVERLOADED RATS. (June 2015) - Puyó, A.; Mikusic, N. Rukavina; Kouyoumdzian, N.; Kravetz, C.; Del Mauro, J.; Pandolfo, M.; Lee, H.; Peredo, H.; Cao, G.; Gironacci, M.; Toblli, J.; Fernández, B.; et al.
Abstract : Objective: Metabolic and hemodynamic changes induced by fructose overload could be associated with a renal dopaminergic system impairment which may affect activity and expression of renal Na+, K+-ATPase contributing to sodium retention and hypertension. The objective of our study was to determine changes in renal dopamine (DA) production through the measurement of urinary L-dopa/DA index and its relationship with natriuresis, renal expression and activity of Na+, K+-ATPase and systolic blood pressure (SBP). Design and method: Male Sprague Dawley rats were studied: a) Controls (C4, C8, C12: tap water to drink) and b) Fructose overloaded: (F4, F8, F12: 10% w/v of fructose solution to drink), treated during 4, 8 and 12 weeks (n = 8 rats/group/period). Urinary L-dopa and DA were determined by HPLC; diuresis and sodium were measured in 24 hour urine samples. SBP was determined by tail-cuff method. The specific activity of Na+, K+-ATPase and its protein expression were determined by enzymatic and immunofluorescence/western blot techniques, respectively. Results: Fructose overload increased SBP (mmHg, C4: 121 ± 8 vs F4: 145 ± 1*; C8: 130 ± 4 vs F8: 161 ± 10#; C12: 133 ± 5 vs F12: 163 ± 4#), urinary L-dopa/DA index (C4: 0.49 ± 0.05 vs F4: 1.9 ± 0.09#; C8: 0.53 ± 0.06 vs F8: 2.35 ± 0.1#; C12: 0.54 ± 0.07 vs F12: 2.57 ± 0.2#) and decreased urinary sodium excretion. A positive correlation was observed throughout all the treatment period between SBP and urinary L-dopa/DA index (R2 = 0.7816, p = 0.002). These changes were accompanied by an increase in renal Na+, K+-ATPase activity (nmol/mg/min, C4: 120 ± 12 vs F4: 172 ± 16*; C8: 124 ± 16 vs F8: 186 ± 17*; C12: 140 ± 18 vs F12: 223 ± 21#) and its protein expression (arbitrary units, renal cortex: C8: 1.00 ± 0.03 vs F8: 1.94 ± 0.34*; medulla: C4: 1.00 ± 0.03 vs F4: 1.54 ± 0.02#; C8: 1.00 ± 0.02 vs F8: 1.39 ± 0.07#; C12: 1.00 ± 0.02 vs F12: 1.24 ± 0.10*). *p < 0.05, #p < 0.01. Conclusions: Fructose overload leads to an increase in the urinary L-dopa/DA index from 4th week of treatment that correlates positively with SBP, along with an elevation in both, renal Na+, K+-ATPase activity and expression. These findings are in accordance with a decrease in natriuresis, postulating the L-dopa/DA ratio as a good index to evaluate an early renal dysfunction.